Risk of coronary heart disease in type 2 diabetes mellitus patients in Kelantan - Ghani, Nurul Akmar (2011)
Introduction: Type 2 diabetes mellitus (T2DM) has become a major health problem worldwide and this disease leads to a wide range of complications, including coronary heart disease (CHD). The research findings obtained are expected to help in management of T2DM patients, in order to decrease the risk of developing CHD, as well as other diabetic complications. Objectives: To determine the survival probabilities and identify the risk factors of developing CHD among T2DM patients in Kelantan Methods: A total of 249 T20M patients attending diabetic clinics in Kelantan who fulfilled the inclusion criteria were included in the analysis. The study design was retrospective record review. The patients' CHO status were determined based on documented diagnosis by medical officer and electrocardiograph (ECG) reading. Kaplan Meier Product Limit Estimates, Simple and Multiple Cox regressions were performed to determine the statistically significant risk factors of developing CHO among T20M patients in Kelantan. Results: Overall survival probabilities of developing CHO in T20M patients in Kelantan was 79.2% (95% CI: 69.0%, 86.4%). The 10 year survival probabilities of developing CHO in T20M patients was 82.2 (95% CI: 84.0%, 92.8%). Significant differences of survival probabilities of developing CHD using Log Rank test were found in hypertension and stroke. The significant prognostic factors found in this study were stroke [Adjusted HR: 3.72 (95% CI: l.41, 9.77), P=0.008] and hypertension [Adjusted HR: 3.84 (95% CI: 0.91, 16.15), P=0.066]. Conclusions: Overall survival rate of developing CHO in T20M patients obtained in this study was approximately equivalent to other studies. The findings revealed that stroke and hypertension were the prognostic factors of developing CHO among T20M patients in Kelantan.